Implementasi Nilai-Nilai Pancasila dalam Projek Penguatan Profil Pelajar Pancasila (P5) di SMK Negeri 1 Pasuruan - Damayanti, Ayu Maya; Ilmiyah, Mahfudzotul; Maulida, Risalatul Dinda (Universitas PGRI Semarang, 2024)
An essential component of personal development is education. Education gives people the values, abilities, and information they need to survive. Students' poor comprehension and enjoyment of Pancasila are caused by the family and society's lack of awareness and attention to putting Pancasila values into practice on a daily basis. Therefore, through Pancasila education, the government, schools, families, and society must work together to solve this issue. For students' overall growth, the Kurikulum Merdeka must incorporate the Projek Penguatan Profil Pelajar Pancasila (P5) activities. The purpose of this study is to investigate how Pancasila values are applied in SMK Negeri 1 Pasuruan's Projek Penguatan Profil Pelajar Pancasila (P5). Interviews with the homeroom instructor and a number of students in classes X were utilized to gather data for this case study study, which used a qualitative research methodology. According to the research findings, SMKN 1 Pasuruan's P5 has implemented Pancasila values through a variety of project activities that actively involve students. To guarantee the P5 program's durability and effectiveness, it is also crucial that all relevant parties—including the government, educators, school personnel, and the community—continue to support it. The article's consequences for scientific advancement and the research's restrictions are still quite low, nevertheless, so that future generations of researchers can carry on.